Effectiveness of the Field Selection Parameters on Potato Yield in Atlantic Canada - Yuan, J.; Murphy, A.; Koeyer, D. de; Lague, M.; Bizimungu, B. (Canadian Science Publishing, 2016)
Cultivated potatoes (Solanum tuberosum L.) are the 4th most important crop feeding the world. Therefore, yield is a crucial trait for potato breeding and germplasm enhancement. The analysis of phenotype data of potato plants enables the extraction of crucial phenotypic characters for potato yield breeding. Using data collected from 179 advanced breeding clones that were planted in evaluation trials over three years at the Benton Ridge breeding substation in Atlantic Canada, we deciphered the dynamic properties of trait expression over the growth period based on nine parameters used in Agriculture and Agri-Food Canada’s potato breeding program. The analysis of breeding data provided valuable information to understand the factors that contribute to the phenotypic performance of potato and potato tuber yield. Linear mixed model fit by maximum likelihood and principal component analysis (PCA) were employed as complementary analysis tools to analyze these characters to try to uncover the relationship of complex agronomic traits. Our results showed that the majority of the selection parameters effectively contributed to the improvement of potato tuber yield. The first five principal components (PCs) accounted for 74.9% of the phenotypic variation observed from 2012 to 2014. The maturity, early vigor, eye depth, and top vigor are the most important phenotypic parameters affecting potato tuber yield selection. Based on the results, these selection parameters are yet highly independent variables which also displayed some degree of interrelationship.